PWE-115 Alpha-Fetoprotein Measurement in the Diagnosis of Hepatocellular Carcinoma in Real-Life Practice: A Multi-Centre, Retrospective Analysis. (4th June 2013) - Wright, K; Harrod, E; Webb, G; Collier, J; Gorard, D; Evans, A
Abstract : Introduction: In hepatocellular carcinoma (HCC), earlier diagnosisimproves outcome but the optimum method of surveillance in high-risk groups is controversial. Recent AASLD and EASL guidelines[1.2] have recommended six- monthly ultrasound surveillance (USS) alone. British guidelines[3] currently recommend combining serial alpha-fetoprotein (aFP) measurements with six-monthly USS. This study aimed to assess the role of aFP measurement in HCC surveillance programmes. Methods: This large retrospective multicentre study assessed newly diagnosed HCC over a 5-year period (2006–2011) at three centres: two general hospitals and one tertiary referral centre. Electronic and multi-disciplinary team data were reviewed. Results: 111 patients with a confirmed diagnosis of HCC were identified. Of these, 91(81.9%) were male and the median age was 69 years (range 24–87). 52(46.8%) patients with newly diagnosed HCC had established liver disease prior to diagnosis. Of these, 21(40.4%) were participating in combined USS-aFP surveillance, 2(3.8%) USS alone and 1(1.9%) aFP alone. A diagnosis of HCC was confirmed by liver biopsy in 43(38.7%), CT in 41(36.9%), MRI in 25(22.5%) and USS combined with elevated aFP in 2(1.8%). At diagnosis, aFP was elevated in 81(73.0%), normal in 22(19.8%) and unmeasured in 8(7.2%) patients. Of those 21 diagnosed in an established surveillance programme of six- monthly USS and aFP, 17(81.0%) showed a rise in aFP. When assessing the trigger for confirmatory cross-sectional imaging ± biopsy across all data, a solely elevated aFP prompted further investigation in 11(9.9%); in those under surveillance, this number was 7(29.2%) with no abnormality detected on USS within the preceding three-month period in 6(85.7%) of these. Conclusion: These results demonstrate that a significant number of patients would have had a delayed diagnosis of HCC if aFP measurement was removed from UK screening programmes. Potential contributing factors limiting the success of USS- based screening programmes include: small lesion size, sonographer error, patient factors limiting USS accuracy (e.g. body habitus) and irregular attendance for USS. This study supports continued serial measurement of aFP in patients with liver cirrhosis in contrast to European and American guidelines. Disclosure of Interest: None Declared. References: Hepatology, vol. 53(3)1020–1022, Mar. 2011. Journal of Hepatology, vol. 56(4)908–943, Apr. 2012 Gut, vol. 52(3)iii1-iii8, 2003.